Reliability of Magnetic Resonance Imaging in Determining Status of Posterior Ligamentous Complex in Thoracolumbar Spinal Fractures - Mehta, Bijay Kumar; Karki, Prashanna Dip; Mishra, Rakesh; Mehta, Binod; Kathayat, Tufan Singh; Poudel, Krishna Prasad; Karki, Prabhat Dip (Birat Journal of Health Sciences, 2025)
Background: Spinal stability depends significantly on the posterior ligamentous complex (PLC) which necessitates determining its status before deciding treatment plan for thoracolumbar injuries. Magnetic Resonance Imaging (MRI) has gained more importance in diagnosing PLC status than other indirect methods. So, this study aimed to evaluate the reliability of MRI in determining the status of PLC in thoracolumbar spinal fractures.Methods: Thirty-three patients who sustained thoracolumbar spinal injuries and required surgery were included. They were evaluated by palpation of the interspinous gap, plain radiograph, and MRI. The radiologist and the surgeon classified PLC status as intact, incompletely disrupted, or disrupted based on MRI and intraoperative findings respectively. The relation between clinical, radiological, and MRI findings was compared with intraoperative findings.Results: A wide interspinous gap was palpated in 9 patients and was found in 14 patients on plain radiographs. MRI showed PLC injury in 20 patients whereas 19 patients had PLC injury shown by intraoperative findings. MRI showed a significant relation with intraoperative findings. There was almost perfect agreement between the radiologist’s interpretation and the intraoperative findings for various components of PLC. MRI sensitivity for diagnosis of each component of PLC varied between 89.1% (interspinous ligament) and 98% (ligamentum flavum). Specificity varied between 68% (facet capsules) and 100% (SSL).Conclusions: MRI has a high sensitivity, specificity, and reliability for diagnosing injury of PLC in thoracolumbar spinal injuries so it can be considered as an important diagnostic tool for treatment plans.